2022
DOI: 10.1155/2022/3032407
|View full text |Cite
|
Sign up to set email alerts
|

Zuo Jin Wan Reverses the Resistance of Colorectal Cancer to Oxaliplatin by Regulating the MALAT1/miR-200s/JNK Signaling Pathway

Abstract: Background. Oxaliplatin (L-OHP) is a common chemotherapy drug used in the treatment of colorectal cancer (CRC). Our previous work showed that Zuo Jin Wan (ZJW), a traditional Chinese medicine prescription, could improve sensitivity to L-OHP in the treatment of CRC, but the detailed mechanism is not clear. In previous mechanistic studies, we found that the miR-200s expression in CRC is associated with L-OHP sensitivity through regulation of MDR1/p-gp and the downstream c-JunN-terminal kinase (JNK) signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Noteworthy, anti-tumor compounds are able to regulate expression level of non-coding RNAs in affecting OXA sensitivity of CRC cells. Zuo Jin Wan increases expression level of miR-200s via MALAT1 down-regulate to suppress JNK signaling in apoptosis induction, proliferation inhibition and OXA sensitivity in CRC cells [ 247 ]. Resveratrol is another compound that has been used in disease and cancer therapy, and nano-scale delivery systems have been employed in increasing its bioavailability and therapeutic index.…”
Section: Pharmacological Compounds and Oxaliplatin Chemosensitivitymentioning
confidence: 99%
“…Noteworthy, anti-tumor compounds are able to regulate expression level of non-coding RNAs in affecting OXA sensitivity of CRC cells. Zuo Jin Wan increases expression level of miR-200s via MALAT1 down-regulate to suppress JNK signaling in apoptosis induction, proliferation inhibition and OXA sensitivity in CRC cells [ 247 ]. Resveratrol is another compound that has been used in disease and cancer therapy, and nano-scale delivery systems have been employed in increasing its bioavailability and therapeutic index.…”
Section: Pharmacological Compounds and Oxaliplatin Chemosensitivitymentioning
confidence: 99%
“…In Wei’s study on the traditional Chinese medicine Zuojin Wan, it was found that MALAT1 promotes resistance to oxaliplatin in CRC by decreasing the expression of miR-200s. Zuojin Wan may reverse chemotherapy resistance by inhibiting the expression of MALAT1 and regulating the miR-200s/JNK pathway ( 158 ). Cai et al.…”
Section: Lncrnas Regulate Drug Resistancementioning
confidence: 99%
“…Further, it should be highlighted that the majority of prior pharmacogenomics research, including our work, has concentrated on a single candidate gene, whose clinical importance is restricted and may not be sufficient to predict the frequency of severe oxaliplatin peripheral neuropathy and oxaliplatin resistance [22,24,25].…”
Section: [20-21]mentioning
confidence: 99%